REAL STRUCTURE AND RESIDUAL STRESSES IN ADVANCED WELDS DETERMINED BY X-RAY AND NEUTRON DIFFRACTION - Karel Trojan; Charles Hervoches; Kamil Kolařík; Nikolaj Ganev; Pavol Mikula; Jiří Čapek (Acta Polytechnica CTU Proceedings)
The paper outlines the capability of X-ray diffraction (XRD) for evaluation of real structure changes and residual stresses (RS) on cross-section of advanced thick welds due to the welding of ferromagnetic plates. The results of neutron diffraction describe a three-dimensional state of RS and also verify previous assumptions of RS redistribution as a result of the surface preparation for determination 2D maps measured by XRD.